2000
DOI: 10.1159/000012378
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Benefits of Group Psychotherapy in Reducing Alexithymia in Coronary Heart Disease Patients: A Preliminary Study

Abstract: Background: Although there is preliminary evidence that alexithymia may influence the course of coronary heart disease (CHD), there are no studies exploring attempts to modify alexithymic characteristics in cardiac patients. Method: Twenty post-myocardial infarction (MI) patients (19 men and 1 woman) were placed in a treatment group, which received weekly group psychotherapy for 4 months. Seventeen post-MI patients (16 men and 1 woman) were placed in a comparison group which received two educational sessions o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
114
0
4

Year Published

2003
2003
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 163 publications
(124 citation statements)
references
References 15 publications
6
114
0
4
Order By: Relevance
“…Whether alexithymia is a cause or a consequence of recurrent episodes of NFA or AMI, once alexithymia improves, the clinical course of some patients also improves. Over a 2-yr follow-up study, BERESNEVAITE [36] observed that AMI patients whose TAS scores improved after psychotherapy suffered fewer new infarctions, sudden deaths and hospital admissions for angor pectoris and arrhythmia (18%) than the group that maintained the same TAS scores (67%). An improvement in alexithymic levels following psychotherapeutic interventions in patients with inflammatory bowel disease has also been previously reported [37].…”
Section: Discussionmentioning
confidence: 99%
“…Whether alexithymia is a cause or a consequence of recurrent episodes of NFA or AMI, once alexithymia improves, the clinical course of some patients also improves. Over a 2-yr follow-up study, BERESNEVAITE [36] observed that AMI patients whose TAS scores improved after psychotherapy suffered fewer new infarctions, sudden deaths and hospital admissions for angor pectoris and arrhythmia (18%) than the group that maintained the same TAS scores (67%). An improvement in alexithymic levels following psychotherapeutic interventions in patients with inflammatory bowel disease has also been previously reported [37].…”
Section: Discussionmentioning
confidence: 99%
“…He found that group psychotherapy leads to increased emotional awareness and, consequently, reductions in level of alexithymia over a period of time. (26) This study concludes that association of alexithymia is high in patients with somatoform disorder and it can be considered as a risk factor to develop somatoform disorders. (27) Alexithymia is a primary personality trait that may predispose the subject to develop longer lasting somatic illnesses.…”
Section: Discussionmentioning
confidence: 72%
“…To find out whether secondary alexithymia can be influenced by any treatment modality, Beresnevaite (2000), in his study selected group of patients, in whom alexithymic features may be a state reaction to high psychological distress. He found that group psychotherapy leads to increased emotional awareness and, consequently, reductions in level of alexithymia over a period of time.…”
Section: Discussionmentioning
confidence: 99%
“…They experience their psychological and physical health as broadly negative. For patients who deal with the adverse psychological consequences of rheumatoid arthritis by ambiguity, therapeutic trials aimed at learning more beneficial strategies of emotion regulation could be considered and evaluated, as has been done in patients with coronary heart disease (Beresnevaite, 2000).…”
Section: Discussionmentioning
confidence: 99%